Keharusan Etis Keberadaan Universum - Fidelis Den (Jurnal Alternatif Wacana Ilmiah Interkultural, 2021)
The essence of the universe is finite, not eternal. So is also everything in it.Therefore, the state is created matter. Humans as creatures that inhabitthe earth have characteristics that are not owned by other inhabitantsof the earth such as animals and plants. Man has consciousness andhigher than that, he has self-awareness. Until now it is still believed byscientists, that this universe has no consciousness and much less self-awareness. Therefore, it is quite possible that man is not a special productof this universe. Because matter without consciousness cannot possiblyproduce conscious beings. The effect cannot be higher than the cause.Thus, we presume there is a rational, eternal cause who is the creator ofthe world and everything in it, including humans. God is the creator ofthe universe and he created it out of love with complete freedom. Becausethe universe is born of divine love, it is inse good and it is good that itexists. The ethical imperative of the existence of the universe is basedon God’s free will, which is based on His love for creating the world. Theuniverse is not divine. He is different from God. He exists not becauseof the process of emanation but the result of God’s free creation.